Investigation of Gas Sensing Property of Single Walled Carbon Nanotube - Iyakutti1, K.; Surya2, V.J.; Britta Mary3, G.; Suthan3, T.; Kawazoe4, Y. (Asian Journal of Chemistry, 2013)
In this first principles study, we have presented the gas sensing properties of single walled carbon nanotube by looking into the nature of interaction of gas molecules, N2, O2, BH3 and NH3 with the carbon nanotube. We have functionalized the single walled carbon nanotube with these molecules and analyzed the changes in the electronic structure of the single walled carbon nanotube after the absorption of the gas molecules and use that change in the electronic structure as the signature for the gas sensing. In the case of N2 it is found for single molecule and many molecules covering the entire surface of carbon nanotube. In the case of O2 we have the results for the single molecule. For BH3 and NH3 we have results for full coverage. The clustering patterns are different for different adsorbates and dependent on the nature of the adsorbed molecules. The study reveals that the gas sensing property of single walled carbon nanotube is very good for gas molecules like N2 and O2.